2013
DOI: 10.1177/1059840513485986
|View full text |Cite
|
Sign up to set email alerts
|

Observing Anthropometric and Acanthosis Nigrican Changes Among Children Over Time

Abstract: This study assessed the anthropometrics and acanthosis nigricans (AN) in a sample of 7,337 children at two assessments. Four groups of children were identified based on the presence of AN at both time points: those who never had the marker, those who gained the marker, those who lost the marker, and those who maintained the marker. Group differences in height, weight, body composition, and the amount of change in these variables over time were explored. Our findings demonstrated that children who maintain or g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Furthermore, the 2-year changes in AN status were more dynamic in the current study, as 8.4% of children changed their status of having or not having AN compared to 2.4% in the study by Law, which represented a cohort of White children in West Virginia. Our study is consistent with previous longitudinal pediatric studies that have consistently reported that the presence of AN is associated with obesity [ 52 , 53 ]. Our current study provides evidence that an increase in the BMI z-score, after adjusting for baseline z-scores, was associated with chronically presenting with AN, while a decrease in the BMI z-score was associated with a remission of AN.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the 2-year changes in AN status were more dynamic in the current study, as 8.4% of children changed their status of having or not having AN compared to 2.4% in the study by Law, which represented a cohort of White children in West Virginia. Our study is consistent with previous longitudinal pediatric studies that have consistently reported that the presence of AN is associated with obesity [ 52 , 53 ]. Our current study provides evidence that an increase in the BMI z-score, after adjusting for baseline z-scores, was associated with chronically presenting with AN, while a decrease in the BMI z-score was associated with a remission of AN.…”
Section: Discussionsupporting
confidence: 93%
“…The 5% prevalence of AN in this sample is greater than in past studies. Law et al [ 52 ] conducted a 2-year follow-up study with an initial 1% AN prevalence in 4059 children in kindergarten to second grade. Furthermore, the 2-year changes in AN status were more dynamic in the current study, as 8.4% of children changed their status of having or not having AN compared to 2.4% in the study by Law, which represented a cohort of White children in West Virginia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation